2020
DOI: 10.1121/10.0001760
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of threshold and loudness on sound duration at low and infrasonic frequencies

Abstract: Many environmental sounds contain significant energy in the infrasonic and low-frequency (ISLF) ranges that have been associated with cases of annoyance and noise complaints. This study assessed the effect of sound duration on audibility and loudness of ISLF sounds. A first experiment evaluated detection thresholds for tones of 4, 16, and 32 Hz with durations up to 4000 ms. Furthermore, equal-loudness-level contours (ELCs) were obtained as function of duration up to 2000 ms. Tones of 1000 Hz were also included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…We are, however, not aware of a specific study that measured the modulation frequency at which the percept of fluctuation strength transitions into a percept of roughness. At least for pure tones of very low frequency, it has been reported informally that below about 10 Hz, sound cycles can be perceived as 'distinct pressure pulses' and even be counted (Jurado et al, 2020;Møller & Pedersen, 2004). This agrees with early results by Lechelt (1975), who showed that a series of short sound clicks presented at low repetition rates (their highest rate was 8 Hz) can be counted with accuracy.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…We are, however, not aware of a specific study that measured the modulation frequency at which the percept of fluctuation strength transitions into a percept of roughness. At least for pure tones of very low frequency, it has been reported informally that below about 10 Hz, sound cycles can be perceived as 'distinct pressure pulses' and even be counted (Jurado et al, 2020;Møller & Pedersen, 2004). This agrees with early results by Lechelt (1975), who showed that a series of short sound clicks presented at low repetition rates (their highest rate was 8 Hz) can be counted with accuracy.…”
Section: Introductionsupporting
confidence: 87%
“…On the one hand, it has been reported that for repetition rates below about 20 Hz, the sensation of pitch ceases (Guttman & Pruzansky, 1962;Warren & Bashford, 1981). On the other hand, reports have also described infrasound as having a 'discontinuous' perceptual quality (Jurado et al, 2020;Møller & Pedersen, 2004). This notion of perceptual segregation at low repetition rates is shared among different sensory modalities.…”
Section: Introductionmentioning
confidence: 99%
“…The latter three studies reveal an activation of the primary auditory cortex, which supports the hypothesis that infrasound is processed by the auditory system. In agreement with this hypothesis, several psychoacoustic studies have shown that pure tones with frequencies down to at least 2 Hz can be detected by the auditory system (e.g., [15][16][17][18][19][20]; for a review, see Møller and Pedersen [21]). The sound pressure levels at threshold-in the following simply referred to as thresholds-are higher than those for frequencies in the classical audio-frequency range (between 20 Hz and 20 kHz) and increase with decreasing frequency.…”
Section: Introductionmentioning
confidence: 78%
“…An exponent of 3 would result in a slope s, expressed as threshold change per doubling of duration, of -2 dB. Table 3 shows the slopes, s, and the offsets, L O , of straight lines fitted to the grand mean thresholds of the MB stimuli (see top row of Fig 3) as well as the exponents, â, derived from the slopes by the equation â ¼ À 20 s lg 2 ð Þ. Note that the thresholds for the shortest duration in the 16Hz_3C condition, i.e., for MB1, deviate from a straight line.…”
Section: Plos Onementioning
confidence: 99%
“…To this end, Bayesian inference in an updated maximum likelihood (UML) procedure was used (Shen & Richards, 2012). This adaptive procedure has proved reliable in various psychophysical tests; for instance, in the field of psychoacoustics (Carcagno & Plack, 2021;Fischer et al, 2021a,b;Lee & Müllensiefen, 2020;Jurado et al, 2020). The method can estimate the reliability of the results by calculating a credible interval, the Bayesian equivalent to the confidence interval in frequentist statistics (Comotto, 2022).…”
Section: Introductionmentioning
confidence: 99%